Say no to wrongdoing: the serial mediation model of responsible leadership and whistleblowing intentions. Issue 5 (20th October 2020) - Akhtar, Muhammad Waheed; Javed, Muzhar; Syed, Fauzia; Aslam, Muhammad Kashif; Hussain, Khalid
Abstract : Purpose: Drawing on the role theory, this study examines how responsible leadership invokes whistleblowing intentions in employees by intervening through "trust in leader" and "person-organization fit." Design/methodology/approach: Using the Hayes (2013) approach, the authors tested the model by collecting a multi-wave data from banking sector employees. Findings: Results of the study show that responsible leadership kindles whistleblowing intentions in banks' employees. Further, the results reveal that both "trust in leader" and "person-organization fit" individually mediate the relationship between responsible leadership and whistleblowing intentions. Moreover, we found that the relationship between responsible leadership and whistleblowing intentions is serially mediated through "trust in leader" and "person-organization fit." Originality/value: The current study contributes to whistleblowing intentions and responsible leadership literature by suggesting "trust in leader" and "person-organization fit" as process through which responsible leaders kindle employee's outcomes.